A facile one-pot operations of reduction and allylation of nitrobenzaldehydes mediated by indium and their applications - Cho, YS; Kang, KH; Cha, JH; Choi, KI; Pae, AN; Koh, HY; Chang, MH (KOREAN CHEMICAL SOC, 2002)
Various nitrobenzaldehydes were simultaneously allylated and reduced using indium in the presence of HCl in aqueous media to give compounds having both functionality of homoallylic alcohol and aromatic amine. Sequential protection of the amino group and oxidation of the anilinyl homoallylic alcohol provided useful precursors of heterocyclic compounds such as dihydroindolones and dihydroquinolones, which could be efficiently synthesized through intramolecular cyclization reaction.
Keywords: AQUEOUS-MEDIA; ORGANIC-REACTIONS